2021
DOI: 10.3892/ol.2021.12558
|View full text |Cite
|
Sign up to set email alerts
|

FAM83A and FAM83A‑AS1 both play oncogenic roles in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) is the most common subtype of lung cancer. Nevertheless, the detailed molecular mechanisms of the progression of LUAD remain largely unknown. The present bioinformatics analysis reported that FAM83A and FAM83A-AS1 were upregulated in LUAD tissues and associated with prognosis in patients with LUAD. The purpose of the current study was to investigate the role of FAM83A and its antisense long non-coding (lnc)RNA FAM83A-AS1 in LUAD. Gene Expression Profiling Interactive Analysis was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Many studies have reported that lncRNA, FAM83A-AS1 has potent tumor-promoting activity in oesophageal squamous cell carcinoma (ESCC), lung cancer, and liver carcinoma [25][26][27]. For instance, Xiao G et al [28] discovered that FAM83A-AS1 could promote LUAD cell migration and invasion, consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have reported that lncRNA, FAM83A-AS1 has potent tumor-promoting activity in oesophageal squamous cell carcinoma (ESCC), lung cancer, and liver carcinoma [25][26][27]. For instance, Xiao G et al [28] discovered that FAM83A-AS1 could promote LUAD cell migration and invasion, consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have revealed that most of these members are closely related to the occurrence and development of various types of cancer. As reported by Wang G et al, FAM83A has been confirmed to be highly expressed in lung adenocarcinoma and is associated with a poor prognosis (24). FAM83B inhibits cisplatin resistance in ovarian cancer by inhibiting the Wnt pathway (25), and high FAM83F expression plays a pro-oncogenic role in papillary thyroid cancer (26).…”
Section: Discussionmentioning
confidence: 86%
“…FAM83A-AS1 plays oncogenic roles in esophageal, liver, and lung cancers [ 18–21 , 23–25 ]. We found that knockdown of FAM83A-AS1 decreased the cell proliferation, colony formation, invasion, and migration in H1299 and H838 lung cancer cells, which were consistent with others [ 18–21 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported FAM83A-AS1 expression is higher in esophageal cancer and can promote cancer progression via binding of miR-495-3p [ 18 ]; whereas knockdown of FAM83A-AS1 impaired cell growth and induced cell apoptosis through binding of NOP58 in liver cancer [ 19 ]. FAM83A-AS1 was suggested to affect lung cancer cell invasion and migration through miR-150-5p/MMP14 signaling [ 20 ] or miR-495-3p [ 23 ] and may promote lung cancer progression through increasing FAM83A expression [ 21 , 24 ] or glycolysis via regulating HIF-1α degradation [ 26 ]. However, the detailed mechanism of FAM83A-AS1 in lung cancer remains uncertain.…”
Section: Introductionmentioning
confidence: 99%